2023
DOI: 10.1002/lno.12400
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐year time series reveals temporally synchronous diatom communities with annual frequency of recurrence in a temperate estuary

Abstract: Diatoms are among the most abundant phytoplankton that inhabit coastal ecosystems, forming large blooms that fuel coastal food webs. Although diatoms are often large and morphologically distinct, many are small or morphologically cryptic making it difficult to understand the temporal dynamics of whole diatom communities and the environmental factors that drive them. Here, we investigated diatom diversity and its environmental correlates using 6 yr of monthly surface water samples from the Narragansett Bay Plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 74 publications
1
2
0
Order By: Relevance
“…Although higher nutrient coastal waters are most often associated with flourishing diatom communities (Bracher et al, 2009;Smetacek, 2012), the highest number of both ASVs and genera were observed in the oligotrophic Sargasso Sea. Furthermore, there was no significant relationship between ASV richness and chlorophyll a concentration, supporting recent work that observed relatively high diatom richness even in low chlorophyll a waters (Fontaine & Rynearson, 2023).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although higher nutrient coastal waters are most often associated with flourishing diatom communities (Bracher et al, 2009;Smetacek, 2012), the highest number of both ASVs and genera were observed in the oligotrophic Sargasso Sea. Furthermore, there was no significant relationship between ASV richness and chlorophyll a concentration, supporting recent work that observed relatively high diatom richness even in low chlorophyll a waters (Fontaine & Rynearson, 2023).…”
Section: Discussionsupporting
confidence: 87%
“…How to cite this article: Setta, S. P., Lerch, S., Jenkins, B. D., Dyhrman, S. T., & Rynearson, T. A. (2023).…”
Section: Ack Nowledg M Ent Smentioning
confidence: 99%
“…ASVs were merged at the genus level (tax_glom function in phyloseq), and subsets of dataset groups (protist and metazoan) were used for heatmap and network composition analyses. For seasonal taxonomic composition analyses (hierarchical clustering and heatmap analyses), frequencies of occurrence for genera [59] were calculated as the number of times a genus occurred in a time frame (season) divided by the total number of samples in that time frame (season). To generate heatmaps, we applied agglomerative clustering specifically with the clustering method ward.D2, and correlation was used as a clustering distance measure with the R package pheatmap.…”
Section: Community Diversity and Composition Analysesmentioning
confidence: 99%